A comparative study on microstructure and properties of pulsed laser welding and continuous laser welding of Al-25Si-4Cu-Mg high silicon aluminum alloy. (August 2021) - Hou, Jiancheng; Li, Ruifeng; Xu, Cheng; Li, Taotao; Shi, Zhongxing
Abstract: As a lightweight material, the high-silicon aluminum alloy Al-25Si-4Cu-Mg has been widely used in aerospace, transportation and construction. Porosity is the most common welding defect in laser welding of high silicon aluminum alloy, and has a certain impact on the properties of high-silicon aluminum alloy. A comparative study of the continuous laser welding (CLW) and pulse laser welding (PLW) of Al-25Si-4Cu-Mg must be conducted to explore the influence of different laser energy output modes on welding. The TruPulse556 pulse lasers and IPG continuous lasers were used to perform the laser welding test in this study. Moreover, a comparative analysis of the PLW and CLW of Al-25Si-4Cu-Mg in terms of microstructure and mechanical properties, including the weld microstructure, hardness, the tensile properties, and porosity. The research shows that PLW inhibits the formation of porosity more effectively than CLW. The mechanical properties and microstructure of the Al-25Si-4Cu-Mg welded joint can be improved by PLW, which has significance to the research on the PLW of high-silicon aluminum alloy.